NEW APPROACHES TO THE DEVELOPMENT OF GENERAL PLANS OF SETTLEMENTS: Array - and (Municipal economy of cities. Series: «Economy science», 2018)
The purpose of the article is development of the issue of increasing the efficiency of usement of countryside in the preparation of planning projects and land management documentation. An analysis of the current state of legal and methodological support for the development of urban planning documentation, the purpose to justify the long-term strategy of planning and building the village territory taking into account state, public and private interests with the use of the software ArchiCAD 20.1 and Digitals. The research was carried out during the creation of the general plan of the village of Odradov in the Pervomaysky district of the Kharkiv region. The program is aimed at ensuring purposeful activities of local self-government bodies, enterprises, institutions, organizations, citizens, associations of citizens to create a valuable living environment, which includes forecasting the development and planning of territories, design, construction and reconstruction of objects of housing, civil engineering, industrial designation , construction of other objects, creation of engineering and transport infrastructure. The development of a general plan of development contributes to the implementation of the strategic plan of economic development of the community for a long period. The village general plan defines the need for territories for development and other uses; priority and priority of development and other use of territories; boundaries of functional zones, priority and permissible types of use and development of territories. The article analyzes the area of the Oddaev village of Pervomaisky district of the Kharkiv region in relation to its planning organization, which identified problems and conflict zones that require resolution of the master plan by means of geoinformation technologies. Incorporated GIS - oriented system approach to display and analysis of the condition of the village of Odadeva during the construction of thematic maps. Keywords: general plan, plan of the existing usement of territory, zoning plan of the territory.